Pengembangan Bahan Ajar IPA Berbasis Mind Mapping Materi Perubahan Wujud Benda dan Sifatnya - Nurilatifa, Farida (Universitas Negeri Semarang, 2018)
Abstract______________________________________________________The purpose of this study is to examine the development and test the feasibility and effectiveness of teaching materials based on mind mapping. Methods in this research use Research and Development (R & D) method with potential and problem steps, data collection, product design design, design validation, product trial, product revision, trial usage, and final product making. The subjects of this study are students of VA SDN Karanganyar 01 Semarang class of 22 students. Data collection techniques using test and non-test techniques. Data analysis techniques use validity test, reliability test, N-gain and t-test. The result of the research shows: (1) book product design developed is teaching materials based on mind mapping and adapted to the level of student development, (2) teaching materials based on mind mapping for grade V students have met the criteria very suitable for use in classroom learning, (3) teaching materials based on mind mapping for grade V students proved effective in reminding students' learning outcomes.